"Mismatch" in the labor market and inflation: An integrative model with lessons from the Spanish experience - Manuel Pérez Trujillo; Santos Ruesga Benito; Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2018)
The Great Recession (2009/10) resulted in the need of different economic policies and structural reforms to boost economic growth both in the advanced and in the emerging economies. In this paper, we start from a theoretical concept that is relatively new - the modified output gap (MOG), based on both the Phillips and the Beveridge curve, initially introduced by Sell and Reinisch (2013) and Sell (2016), revealing the explicit positive relationship between the vacancy ratio on the one hand and the inflation rate on the other hand. Empirically, we estimate this relationship by developing three different panel data models: Fixed Effects (FE), Random Effects (RE) and a GMM System (Generalized Method of Moments). The obtained results show that the loss in the efficiency of matching in the labor market combined with an increase in the demand in the markets for goods and services will push up inflation. We show the empirical relevance of the modified output gap for Spain during the Great Recession and explain how it affected the implementation of the economic stimulus plan that was introduced by the then socialist government in Spain with the aim of boosting the economy.
Keywords: J63; J41; E65; E31; 330; mismatch; Beveridge curve; Philipps curve; modified output gap; great recession